Improvement of a Hall Effect Thruster structure based on finite element analysis - Che, Zhicheng (Nanyang Technological University, 2023)
A Hall Effect Thruster (HET) is an electric propulsion system that employs the principle of the Hall Effect to accelerate charged particles, typically ions, to generate thrust. Hall Effect Thrusters are widely used in spacecraft for various purposes, including orbit raising, station keeping, attitude control, and deorbiting. HETs are known for high efficiency and low fuel consumption making them an attractive option for long-duration space missions. The performance of the Hall Effect Thruster depends heavily on its structure and material selection. Therefore, the objective of this study is to analyze and enhance the structure of a typical Hall Effect Thruster structure (JP2007071055A) in the respective of structural reinforcement and materials selection. Creo Parametric 9.0.0.0 Student edition was used to create models, which were then analyzed on Ansys Student Edition. Additionally, based on the structure of JP2007071055A, two more models are proposed with improvements in materials selection and structural reinforcement. All models undergo static structural tests, modal analysis and random vibration tests. A comparative analysis of the simulation results is carried out to evaluate the performance of the models. The study reveals that the use of silicon core iron, in lieu of pure iron, and other additional support can significantly enhance the robustness of the model under static load and vibration.